2020
DOI: 10.3390/ijerph17051463
|View full text |Cite
|
Sign up to set email alerts
|

A Salutogenic Approach to Disaster Recovery: The Case of the Lac-Mégantic Rail Disaster

Abstract: In July 2013, a train carrying crude oil derailed in Lac-Mégantic (Canada). This disaster provoked a major fire, 47 deaths, the destruction of 44 buildings, a massive evacuation, and an unparalleled oil spill. Since 2013, Public Health has undertaken several actions to address this challenging situation, using both quantitative and qualitative methods. Community-based surveys were conducted in Lac-Mégantic in 2014, 2015 and 2018. The first two surveys showed persistent and widespread health needs. Inspired by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…In other words, resolving one collective challenge can sometimes fuel a positive development in society. Overcoming and growing with challenges is in line with a salutogenic perspective, and at the heart of the salutogenic process (Antonovsky, 1987;Généreux, Roy, O'Sullivan, & Maltais, 2020;Namihira, 2019).…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…In other words, resolving one collective challenge can sometimes fuel a positive development in society. Overcoming and growing with challenges is in line with a salutogenic perspective, and at the heart of the salutogenic process (Antonovsky, 1987;Généreux, Roy, O'Sullivan, & Maltais, 2020;Namihira, 2019).…”
Section: Introductionmentioning
confidence: 95%
“…Sharing experiences with your in-group can be a conscious-rising, empowering experience, which helps you to understand the structural components of your experience, and collectively seek solutions (Carr, 2003). The community emerges as an important coping resource in the face of disaster or conflict (Braun-Lewensohn et al, 2019;Braun-Lewensohn & Sagy, 2011;Braun-Lewensohn & Sagy, 2014;Généreux, David, O'Sullivan, et al, 2020;Généreux, Roy, O'Sullivan, & Maltais, 2020;Namihira, 2019). The community, and even national states, are crucial contexts for the experience of coherence in difficult times (Sagy et al, 2020;Sagy & Braun-Lewensohn, 2009;Sagy, 2015;Braun-Lewensohn et al, 2019;Ben David et al, 2017).…”
Section: Vertical Policy Coherence: From a Decision To Implementationmentioning
confidence: 99%
See 1 more Smart Citation
“…A strengths-based approach, not only focusing on risk factors (or stressors) but also on protective factors (or assets) is important to better understand how mental health and well-being can buffer the adverse effects of psychological stressors ( 13 ). This type of research is urgently needed because promoting health and well-being through a salutogenic approach may be just as important as protecting health and safety in a disaster context ( 14 ). It has indeed been shown that fostering health assets may complement the usual public health response for people in unfavorable situations ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Another research article subset published in this edition is related to the evaluation of human health and well-being with man-made/technology-related disasters. In their case study, Genereux et al [ 12 ] analyze how mixed-method-based need assessment might capture potential health risks and needs and subsequently enhance effectiveness and relevance response and recovery of the 2013 Lac-Megantic Rail disaster. The study of Orui et al [ 13 ] finds an association between media information and post nuclear accident health anxiety.…”
mentioning
confidence: 99%